Béranger in Nineteenth-Century America: Translating Revolution - Steele, Robert (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2019)
Pierre-Jean de Béranger (1780–1857) was revered during his lifetime as the national poet of France. His championing of the Revolution and the people earned him significant impact in the United States; an antebellum American reviewer touted Béranger’s patriotism and his struggle for liberty as a model for an American national poetry. Translations of his songs were published in various formats at various prices by major publishers who also imported French-language editions. Translators struggled to bring his politically radical and sexually scandalous texts across linguistic and cultural borders to construct a Béranger who could be understood in the United States. Yet by refusing to translate Béranger, direct-language pioneer Lambert Sauveur subversively exposed his students to the Christian roots of socialism and a defense of the Paris Commune. By century’s end, Béranger’s influence had faded to mere inclusion in delicately suggestive anthologies, but his voice lived on to inspire leftists of the next century.